PENGARUH MODERNISASI TERHADAP PERUBAHAN NILAI-NILAI AGAMA BUDDHA - Satria, Okie (2016)
This study discusses the influence of modernization that changes the values of Buddhism in the Buddhist Institute Prasadha Jinarakkhita Jakarta. This study aims to determine how the effects of modernization on the value of religion in Prasadha Jinarakkhita Buddhist Institute, a component of religious values that influenced by the modernization in Prasadha Jinarakkhita Buddhist Institute, the impact of modernization in Prasadha Jinarakkhita Buddhist Institute, the type of modernization that affect the values of religion, and the Buddhists' response against the values of Buddhism. This study used a mixed approach and the descriptive study method. The data collection was done by using, observation, documentation, in-depth interviews, questionnaires and analysis. Informants consisted of the religious heads, administrators, and Buddhists. The results of this study : First,the effect of modernization that changes the value of Buddhism comes from the development of technology, science, the influence of foreign cultures. Second, religious values that are affected by the modernization is religious emotion. Third, the positive impact of the modernization is science and technology and the negative impact is impairment of religion, indifference, material needs are more important. Fourth, the type of results that affect the public, namely the modernization of technology, the development of science, making individualistic attitude, consumptive lifestyles, following the style of Westernized, impairment and religious norms. And Fifth, the Buddhist community to understand the values of Buddhism.;---Penelitian ini membahas pengaruh modernisasi terhadap perubahan nilai-nilai agama Buddha di Prasadha Jinarakkhita Buddhist Institute Jakarta. Penelitian ini bertujuan untuk mengetahui bagaimana pengaruh modernisasi terhadap nilai agama di Prasadha Jinarakkhita Buddhist Institute, komponen nilai agama yang dipengaruhi modernisasi di Prasadha Jinarakkhita Buddhist Institute, dampak dari modernisasi di Prasadha Jinarakkhita Buddhist Institute, jenis modernisasi yang mempengaruhi pada nilai-nilai agama, dan respon umat Buddhis terhadap nilai-nilai agama Buddha. Penelitian ini menggunakan pendekatan campuran dan metode studi deskriptif. Pengumpulan data dilakukan dengan teknik, observasi, dokumentasi, wawancara mendalam ,angket, dan analisis. Informan penelitian terdiri dari pihak kepala keagamaan, pengurus, dan masyarakat umat Buddhis. Dari hasil penelitian ini ditemukan bahwa pertama: pengaruh modernisasi pada perubahan nilai agama Buddha berasal dari perkembangan teknologi, ilmu pengetahuan, pengaruh dari budaya luar. Kedua, komponen nilai agama yang dipengaruhi modernisasi adalah dari emosi keagamaan. Ketiga, dampak positif modernisasi ilmu pengetahuan dan teknologi dan dampak negatif penurunan nilai agama, sikap tidak peduli, kebutuhan materi lebih penting. Keempat, jenis hasil modernisasi yang mempengaruhi masyarakat yaitu teknologi, perkembangan ilmu pengetahuan, membuat sikap individualistik, pola hidup konsumtif, mengikuti gaya kebarat-baratan, penurunan nilai dan norma agama. Dan kelima, masyarakat agama Buddha memahami nilai-nilai agama Buddha.